Penyuluhan dan Pelatihan Stimulasi Ekonomi UMKM Dalam Menghadapi Pandemi Covid-19 - Muhammad Irwansyah Hasibuan; Basyarul Ulya; Rizki Kurniawan Rangkuti; Sudi Suryadi; Erlia Utami Panjaitan; Ronal Watrianthos; Wahyu Azhar Ritonga; M Fauzi Romadhon Marpaung; Raden Sri Ayu Ramadhana; Shabrina Rasyid Munthe (Journal of Social Responsibility Projects by Higher Education Forum, 2021)
The results obtained from the Economic Stimulation Counseling and Training on August 26, 2021 with the number of participants who took part in the Extension and Training carried out by 50 people by complying with the health protocol standards issued by the government, before carrying out activities the training facilities were made in a distance according to the standards. wash hands and wear masks both before and after activities. In the delivery of the material presented, it was very well received by the Extension and Training Participants as much as 80%. Before carrying out the activities, interviews were conducted. Based on the interview, it was found that 17 people did not know MSMEs with a percentage of 34%. From the purpose of community service on the Al Washliyah University Labuhanbatu campus, the response was very good and brought changes to the community around the campus who took part in the Counseling and Training. After the Stimulation Counseling and Training was carried out again at the end of the elaboration of the material by the community service team which it was known that the information received by the community was very good, judging by the results of the interview, it was known that there was a good increase of 14 people with a percentage of 94% compared to before the counseling and training was carried out. . The shortcomings obtained in the Extension and Training are due to other factors, such as the different abilities of the participants, so it is necessary to carry out Counseling and Retraining to the community around the campus area in the future